Penggunaan Slurry sebagai Pupuk Organik terhadap Kualitas dan Fermentabilitas Rumput Setaria (Setaria splendida Stapf) di Rumen - Berutu, Evi Yuni Hernika; Afzalani, Afzalani; Syarifudin, Hutwan; Muthalib, R. A.; Hoesni, Fachroerrozi; Raguati, Raguati (Universitas Batanghari Jambi, 2024)
Biogas slurry is an organic product derived from livestock manure and produced through an aerobic fermentation process that can be used to improve soil fertility, forage production, and quality. This study aimed to investigate the effect of slurry organic fertilizer on crude protein content, crude fiber, and total fermentation gas production in the rumen in vitro . The study was conducted in a completely randomized design (CRD), consisting of five treatments of slurry levels as organic fertilizer and four replications consisting of two experimental units. The treatments consisted of S0 = without slurry, S1 = slurry 20 g/polybag, S2 = slurry 25 g/polybag, S3 = slurry 30 g/polybag, and S4 = slurry 35 g/polybag. The variables measured in this study were crude protein content, crude fiber, and total fermentation gas production. The data obtained were analyzed using a variance analysis (ANOVA). Duncan’s test was used to determine the effect of different levels of slurry on the measured parameters. The results showed that the use of slurry as an organic fertiliser increases crude protein content by an average of 16.06%, increases crude protein production from 1.47 g/poly bag to 96.38 g/poly bag and improves fermentability in the rumen by an average of 8.08% of setaria grass (Setaria splendida Stapf). The use of slurry at the level of 35 g/poly bag is recommended for the cultivation of setaria grass (Setaria splendida Stapf).